Surface analysis of pineapple leaves pulp-based dielectric composite material and its dielectric performance - Mohamad Shaiful, Abdul Karim; Norazwina, Zainol; N. H., Aziz; M. J. M., Fikry; Nurhafizah, Abu Talip @ Yusof (Elsevier B.V., 2025)
The integration of cellulose fiber composites into material engineering marks a pivotal step toward sustainable development. In this study, dielectric composite materials derived from pineapple leaf pulp were analyzed for their surface characteristics and corresponding dielectric performance. Cellulose fibers were extracted from pineapple leaves using a soda pulping method, with cellulose content quantified through the Kurschner-Hanack technique. The developed composite, comprising cellulose fibers, epoxy resin, and hardener, was evaluated for its permittivity using a waveguide technique in the G-band. Surface morphology was assessed through scanning electron microscopy (SEM), while elemental composition was determined via energy-dispersive X-ray (EDX) spectroscopy. Results indicated a cellulose content of 59 % and a permittivity value of 3.27. The surface analysis revealed that fiber diameter plays a critical role in influencing both cellulose content and permittivity, with increases in fiber diameter leading to higher values for both. Elemental analysis identified carbon, oxygen, sodium, calcium, silicon, aluminum, and potassium in the fibers, with carbon being the most prevalent. This study highlights the direct influence of fiber morphology and elemental composition on the dielectric performance of pineapple leaf-based composites, offering a sustainable pathway for advanced electronic materials development. The observed dielectric properties suggest that this cellulose fiber composite could potentially serve as a sustainable alternative to conventional capacitors in electronic applications.